2019
DOI: 10.1016/j.celrep.2019.06.094
|View full text |Cite
|
Sign up to set email alerts
|

A Key Role for the Ubiquitin Ligase UBR4 in Myofiber Hypertrophy in Drosophila and Mice

Abstract: SUMMARY Skeletal muscle cell (myofiber) atrophy is a detrimental component of aging and cancer that primarily results from muscle protein degradation via the proteasome and ubiquitin ligases. Transcriptional upregulation of some ubiquitin ligases contributes to myofiber atrophy, but little is known about the role that most other ubiquitin ligases play in this process. To address this question, we have used RNAi screening in Drosophila to identify the function of > 320 evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 61 publications
4
96
0
Order By: Relevance
“…Furthermore, increased gene expression of UBR5 in these models resulted in greater abundance of UBR5 protein content following FO-induced hypertrophy of the mouse plantaris muscle in-vivo, and over the timecourse of regeneration in primary human muscle cells in-vitro (Seaborne et al, 2019). A recent study also supported the role of UBR5 as being essential for muscle growth through RNAi screening in Drosophila larvae, where UBR5 inhibition led to smaller sized larvae (Hunt et al, 2019). Finally, unpublished data from our lab in bioengineered mouse SkM also demonstrated that UBR5 was the most significantly upregulated transcript after loading, amongst a selection of genes that are known to be regulated across the human transcriptome and methylome after acute RE (Seaborne et al, 2018b;Turner et al, 2019b).…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, increased gene expression of UBR5 in these models resulted in greater abundance of UBR5 protein content following FO-induced hypertrophy of the mouse plantaris muscle in-vivo, and over the timecourse of regeneration in primary human muscle cells in-vitro (Seaborne et al, 2019). A recent study also supported the role of UBR5 as being essential for muscle growth through RNAi screening in Drosophila larvae, where UBR5 inhibition led to smaller sized larvae (Hunt et al, 2019). Finally, unpublished data from our lab in bioengineered mouse SkM also demonstrated that UBR5 was the most significantly upregulated transcript after loading, amongst a selection of genes that are known to be regulated across the human transcriptome and methylome after acute RE (Seaborne et al, 2018b;Turner et al, 2019b).…”
Section: Introductionmentioning
confidence: 80%
“…Ubiquitin ligases have been associated with atrophy. However, a recent RNAi screening for the ubiquitin ligases that control muscle mass identified UBR4 as a critical one for hypertrophy 37 . UBR4 induces hypertrophy via ubiquitination and degradation of a core set of target proteins, including the HAT1/RBBP4/RBBP7 histone-binding complex, that control histone acetylation and expression of growth-promoting genes.…”
Section: Metabolic Regulators That Sustain Muscle Growthmentioning
confidence: 99%
“…Although the role of the ubiquitin proteasome system in muscle proteolysis is well established, the role, if any, this system plays in muscle growth has only recently been investigated. In both Drosophila and mouse myofibers, loss of UBR4, the N-end rule ubiquitin-protein ligase, induces hypertrophy by reducing the ubiquitination and degradation of a core set of target proteins, including the HAT1/RBBP4/RBBP7 histone-binding complex [ 95 ]. Interestingly, the importance of N-end rule ubiquitination in the regulation of muscle proteolysis was recognized over two decades ago.…”
Section: Regulators Of Proteolysismentioning
confidence: 99%